Let f : N → N be a function such that


Let $\mathrm{f}: \mathbf{N} \rightarrow \mathbf{N}$ be a function such that $\mathrm{f}(\mathrm{m}+\mathrm{n})=\mathrm{f}(\mathrm{m})+\mathrm{f}(\mathrm{n})$ for every $\mathrm{m}, \mathrm{n} \in \mathbf{N} .$ If $\mathrm{f}(6)=18$ then $f(2) \cdot f(3)$ is equal to :

  1. 6

  2. 54

  3. 18

  4. 36

Correct Option: , 2



Put $\mathrm{m}=1, \mathrm{n}=1$

$f(2)=2 f(1)$

Put $\mathrm{m}=2, \mathrm{n}=1$

$f(3)=f(2)+f(1)=3 f(1)$

$f(6)=2 f(3) \Rightarrow f(3)=9$

$\Rightarrow f(1)=3, f(2)=6$

$f(2) \cdot f(3)=6 \times 9=54$

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now